Ultra-high molecular weight chemically cross-linked separator

A battery separator with a laminated heat-resistant layer and silane-modified polyolefin crosslinking mechanism addresses the challenge of maintaining insulation and safety in lithium ion secondary batteries, ensuring stable cycle performance and preventing thermal runaway.

JP7607859B2Active Publication Date: 2025-01-06ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020124570
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-21
Publication Date
2025-01-06
Estimated Expiration
2040-07-21

AI Technical Summary

Technical Problem

Existing lithium ion secondary batteries face challenges in achieving both stable cycle performance and enhanced safety, particularly in preventing nail penetration and maintaining insulation at high temperatures, which can lead to thermal runaway and safety issues.

Method used

A battery separator comprising a polyolefin microporous membrane with a laminated heat-resistant layer, where the heat-resistant layer includes ceramics or aramid resin, and a silane-modified polyolefin that initiates a crosslinking reaction with the electrolyte, forming a crosslinked structure to enhance insulation and safety.

Benefits of technology

The solution provides a battery separator that maintains high impedance at elevated temperatures, preventing short circuits and improving both cycle performance and nail penetration safety, thereby enhancing the overall safety and stability of lithium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607859000001
    Figure 0007607859000001
  • Figure 0007607859000002
    Figure 0007607859000002
  • Figure 0007607859000003
    Figure 0007607859000003
Patent Text Reader

Abstract

To provide a battery separator capable of achieving both battery cycle performance and nail stick test safety, as well as a battery assembly kit and a battery using the same.SOLUTION: A battery separator includes a polyolefin microporous film used for a non-aqueous electrolyte secondary battery including positive and negative electrodes that can occlude and release lithium, and a non-aqueous electrolyte solution made by dissolving an electrolyte in a non-aqueous solvent, and the impedance measured at any of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C is 8,000 to 500,000 Ω cm2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a battery separator and the like. [Background technology]

[0002] Microporous membranes are widely used as separation or permselective separation membranes for various substances, separators, etc., and examples of their applications include microfiltration membranes, separators for fuel cells and capacitors, base materials for functional membranes in which functional materials are filled into the pores to exhibit new functions, battery separators, etc. Among these, polyolefin microporous membranes are preferably used as separators for lithium ion batteries, which are widely used in electric vehicles, notebook personal computers, mobile phones, digital cameras, etc.

[0003] In order to ensure the safety of batteries, separators are required to achieve both the activation of the shutdown function and an improvement in the membrane rupture temperature. For example, adjustment of the high-order physical properties of polyolefin resins contained in lithium-ion battery separators (Patent Document 1) or adjustment of the crystallinity and gel fraction region (Patent Document 2) have been reported. In addition, the use of a crosslinking reaction of silane-modified polyethylene in the separator manufacturing process has been proposed (Patent Documents 3 and 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-216964 [Patent Document 2] WO 97 / 44839 [Patent Document 3] Japanese Patent Application Publication No. 11-144700 [Patent Document 4] Japanese Patent Application Publication No. 11-172036 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, the output and energy density of lithium-ion secondary batteries for use in mobile devices or vehicles have been increasing, while there is a demand for smaller battery cells and stable cycle performance during long-term use. Furthermore, the required battery safety standards are becoming stricter than those of conventional products, and there is room for improvement in the performance of batteries equipped with the separators described in Patent Documents 1 to 4.

[0006] In view of the above problems, the present invention has an object to provide a battery separator that can achieve both battery cycle performance and nail penetration test safety, as well as a battery assembly kit and a battery that use the same. [Means for solving the problem]

[0007] The above problems can be solved by the following technical solutions. [1] A battery separator including a microporous polyolefin membrane for use in a nonaqueous electrolyte secondary battery comprising a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a nonaqueous electrolyte obtained by dissolving an electrolyte in a nonaqueous solvent, the battery separator having an impedance of 4,000 to 500,000 Ω cm measured at any of the following temperatures: 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C. 2 That is, a battery separator. [2] 2. The battery separator according to item 1, comprising a base material A layer as the polyolefin microporous membrane, and a heat-resistant B layer is laminated on at least one surface of the base material A layer. [3] 3. The battery separator according to item 2, wherein the heat-resistant B layer comprises at least one selected from the group consisting of ceramic, aramid resin, and polyvinylidene fluoride (PVDF). [4] The battery separator comprises a silane-modified polyolefin; and 4. The battery separator according to any one of items 1 to 3, wherein a silane crosslinking reaction of the silane-modified polyolefin is initiated when the battery separator comes into contact with an electrolyte solution. [5] A battery comprising an electrode, the battery separator according to any one of items 1 to 4, and a non-aqueous electrolyte solution. [6] 6. The battery according to item 5, wherein the non-aqueous electrolyte solution contains a non-aqueous solvent and a lithium salt. [7] The following two elements: (1) an exterior housing housing a laminate or wound body of a positive electrode, a negative electrode, and the battery separator described in item 4; and (2) a container containing a nonaqueous electrolyte; A battery assembly kit comprising: [8] 8. The battery assembly kit according to item 7, wherein the non-aqueous electrolyte solution contains a fluorine (F)-containing lithium salt. [9] Item 9. The battery assembly kit according to item 7 or 8, wherein the non-aqueous electrolyte solution contains lithium hexafluorophosphate (LiPF6).

[10] 10. The battery assembly kit according to any one of items 7 to 9, wherein the non-aqueous electrolyte solution is an acid solution and / or a base solution.

[11] The following steps: A step of preparing a battery assembly kit according to any one of items 7 to 10; a step of initiating a silane crosslinking reaction of the silane-modified polyolefin by contacting the battery separator in element (1) of the battery assembly kit with the non-aqueous electrolyte in element (2); A method for manufacturing a battery comprising the steps of:

[12] moreover, A step of performing at least one charge / discharge cycle. Item 12. A method for producing the battery according to item 11, comprising: Effect of the Invention

[0008] According to the present invention, it is possible to provide a battery separator that can achieve both the cycle performance and nail penetration test safety of a battery, and it is also possible to provide a battery assembly kit and a battery using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the mode for carrying out the present invention (hereinafter abbreviated as "embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced with various modifications within the scope of the gist. In this specification, the abbreviation "MD" means the machine direction of continuous microporous membrane molding, and the abbreviation "TD" means the direction crossing MD at an angle of 90°.

[0010] [Battery separator] Battery separators (hereinafter, simply referred to as "separators") are required to have insulating properties and ion permeability, and are therefore generally formed from insulating materials having a porous structure, such as paper, polyolefin nonwoven fabric, or resin microporous membrane. In particular, as a separator substrate used in a nonaqueous electrolyte secondary battery comprising a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a nonaqueous electrolyte solution obtained by dissolving an electrolyte in a nonaqueous solvent, a polyolefin microporous membrane that has oxidation-reduction resistance and can form a dense and uniform porous structure is excellent. Therefore, the battery separator according to this embodiment includes a polyolefin microporous membrane.

[0011] [Relationship between temperature and impedance] The battery separator according to this embodiment has an impedance of 4,000 to 500,000 Ω cm measured at any of the temperatures of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C. 2 It is.

[0012] The battery separator has a structure that can improve the cycle performance and nail penetration test safety of the battery and has a resistance of 4,000 to 500,000 Ω cm at any of the following temperatures: 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C. 2From the viewpoint of further improving the cycle performance and nail penetration test safety of the battery, the impedance is specified to be within the range of 5,000 to 350,000 Ω cm regardless of the temperature measured at 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, or 240°C. 2 Preferably, the resistance is in the range of 9,000 to 250,000 Ω cm 2 It is more preferable that the average impedance of nine points measured at 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C is in the range of 5,000 to 200,000 Ω cm. 2 Preferably, the resistance is 10,000 to 180,000 Ω cm 2 More preferably, the resistance is 13,000 to 150,000 Ω cm 2 It is more preferable that:

[0013] In the nail penetration test for batteries, the nail penetrates the positive electrode, separator, and negative electrode, and greatly deforms each component, so that local short circuit between the positive and negative electrodes around the nail is inevitable. At that time, as the temperature inside the battery rises due to Joule heat generated by the short circuit, the thermal decomposition of each component, the evaporation of the electrolyte, and chemical reactions due to the secondary decomposition products proceed in a short period of time, which may lead to fire and explosion due to thermal runaway. In this way, physical phenomena and chemical reactions are combined, making it extremely difficult to ensure safety. In this embodiment, the idea was to suppress the expansion of the short circuit area in the system as much as possible even when an internal short circuit occurs in the battery system due to a nail or the like. If the insulation between the positive and negative electrodes can be maintained even if the separator crystallizes and melts in the area where the temperature rises at the short circuit area around the nail, the short circuit expansion between the positive and negative electrodes and further temperature rise are suppressed, and as a result, thermal runaway does not occur, and nail penetration safety is improved.

[0014] On the other hand, the separator after melting is a viscoelastic body, and physical phenomena such as penetration into each battery component and large deformation at the penetration destruction part are mixed, making it difficult to predict its behavior. In this embodiment, various resin compositions and other composite experiments have been conducted, and a separator that maintains the insulation between the positive and negative electrodes, i.e., the impedance value specified above, even at high temperatures has been provided experimentally. In response to such results, in order to achieve a high impedance value, a method of making the separator thicker, improving the insulating performance of the separator's constituent materials, or improving the insulating performance by reducing the separator's pore structure can be considered. However, in either case, there is a disadvantage in that the ion resistance is increased in the normal temperature range of the battery, and slight ion permeation unevenness in the surface becomes more noticeable, causing potential distribution in the battery and the possibility of unexpected side reactions occurring. As a result, the cycle capacity maintenance rate during long-term battery use is deteriorated. In this embodiment, various resin compositions and other composite experiments have been conducted, and a separator that can maintain the impedance value at high temperatures at a level that ensures the safety of the battery against nail penetration and at the same time realizes a good battery cycle capacity maintenance rate is provided.

[0015] The impedance measured at temperatures of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C can be adjusted to within the above numerical ranges, for example, by appropriately selecting the resin raw materials of the separator, substrate, or heat-resistant layer.

[0016] [Separator layer configuration] The battery separator is made of the following two layers from the viewpoint of achieving both cycle performance and nail penetration test safety: A polyolefin microporous membrane as the substrate A layer; and A heat-resistant layer B laminated on at least one side of the base layer A; It is preferred that the compound contains

[0017] From the same viewpoint, the thickness ratio A / B of the base material A layer to the heat-resistant B layer is preferably 0.5 or more and 10 or less.

[0018] In the case of a battery separator used in a relatively high-capacity lithium-ion secondary battery in recent years, the total thickness of the base material A layer and the heat-resistant B layer is preferably 25 μm or less, more preferably 23 μm or less or 22 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. In this case, by having the total thickness of the base material A layer and the heat-resistant B layer be 25 μm or less, uniform ion permeability tends to be further improved. In this case, the lower limit of the total thickness of the base material A layer and the heat-resistant B layer may be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more.

[0019] [Base material A layer] The polyolefin microporous film as the substrate A layer can be a monolayer film consisting of a single polyolefin-containing microporous layer, a multilayer film consisting of multiple polyolefin-containing microporous layers, or a multilayer film consisting of a polyolefin resin layer and a layer containing another resin as a main component.

[0020] In the case of a bilayer membrane formed from two polyolefin-containing microporous layers, the polyolefin composition of the two layers can be different, and in the case of a multilayer membrane formed from three or more polyolefin-containing microporous layers, the polyolefin composition of the outermost and innermost layers can be different, for example, a three-layer membrane.

[0021] The multilayer film as the substrate is a 1 a layer, the layer including a polyolefin 2 It is preferable that the laminate structure has at least one layer and a layer, and more preferably, 1 A on both sides of the layer 2 The laminated structure has three or more layers each having one layer. 1 Layer and a 2 As long as each layer has one layer, 1 layer-a 2 A two-layer structure of "a layer" or "a 2 layer-a 1 layer-a 2 For example, the polyolefin microporous membrane may have a three-layer structure in which either or both of the a2 On top of the layer, 1 Layer and a 2 Between the layers one or more further layers may be formed.

[0022] a 1 Layer and a 2 The layer comprises, and preferably is composed of, a polyolefin. 1 Layer and a 2 The form of the polyolefin of the layer may be a microporous polyolefin body, for example, a woven fabric of polyolefin-based fibers, a nonwoven fabric of polyolefin-based fibers, or the like.

[0023] (Polyolefin) The polyolefin is not particularly limited, and examples thereof include homopolymers of ethylene or propylene, and copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, norbornene, and modified polyolefins. Among these, from the viewpoint of being able to perform heat setting (sometimes abbreviated as "HS") at higher temperatures without blocking pores, high density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene (UHMWPE), or modified polyolefins are preferred, and high density polyethylene, UHMWPE, or modified polyolefins are more preferred. In general, it is known that the weight average molecular weight of UHMWPE is 1,000,000 or more. The polyolefins may be used alone or in combination of two or more kinds.

[0024] In addition, the polyolefin microporous film preferably contains a polyolefin having a weight average molecular weight (Mw) of less than 8,000,000, and more preferably contains a polyolefin having a Mw of less than 8,000,000 in a proportion of 3% by mass or more, more preferably 5% by mass or more, based on the total polyolefin. By using a polyolefin having a Mw of less than 8,000,000, the polymer shrinkage tends to be relaxed early in a cycle test or a nail penetration test of a battery, and safety tends to be easily maintained. The weight average molecular weight of the entire polyolefin microporous film constituting the separator is preferably 800,000 or more and 8,000,000 or less, more preferably 900,000 or more and 6,000,000 or less. In addition, when a polyolefin having a Mw of less than 8,000,000 is used, the elastic modulus in the thickness direction of the obtained microporous film tends to be small, so it is preferable to use it in the above proportion based on the total polyolefin in order to suppress the transfer of the unevenness of the core and the deformation caused by it.

[0025] [Characteristics of base material A layer] The following microporous membrane properties are for flat or single-layer membranes. When the microporous membrane is in the form of a laminate membrane, the following properties can be measured after removing layers other than the polyolefin microporous membrane from the laminate membrane.

[0026] The porosity of the polyolefin microporous film is preferably 20% or more, more preferably 30% or more, and even more preferably 32% or more or 35% or more. When the porosity of the microporous film is 20% or more, the followability to the rapid movement of lithium ions tends to be improved. On the other hand, the porosity of the microporous film is preferably 90% or less, more preferably 80% or less, and even more preferably 50% or less. When the porosity of the microporous film is 90% or less, the film strength tends to be improved and self-discharge tends to be suppressed. The porosity of the microporous film can be measured by the method described in the Examples.

[0027] The air permeability of a microporous polyolefin membrane is 3The air permeability of the microporous membrane is preferably 1 second or more, more preferably 30 seconds or more, even more preferably 50 seconds or more, even more preferably 55 seconds or more, particularly preferably 70 seconds or more, and most preferably 75 seconds or more. When the air permeability of the microporous membrane is 1 second or more, the balance between the membrane thickness, the porosity, and the average pore size tends to be improved. In addition, the air permeability of the microporous membrane is preferably 400 seconds or less, more preferably 300 seconds or less, and even more preferably 270 seconds or less. When the air permeability of the microporous membrane is 400 seconds or less, the ion permeability tends to be further improved. The air permeability of the microporous membrane can be measured by the method described in the Examples.

[0028] The tensile strength of the polyolefin microporous membrane is preferably 1000 kgf / cm in both MD and TD (direction perpendicular to MD, membrane width direction). 2 More preferably, it is 1050 kgf / cm 2 More preferably, it is 1100 kgf / cm 2 More than 1000kgf / cm 2 By being equal to or greater than this, breakage during lamination or winding with a slit or electrode tends to be more suppressed, and short circuits due to foreign matter in a battery tend to be more suppressed. On the other hand, the tensile strength of the microporous membrane is preferably 5000 kgf / cm 2 More preferably, it is 4500 kgf / cm or less. 2 More preferably, it is 4000 kgf / cm or less. 2 The tensile strength of the microporous membrane is 5000 kgf / cm or less. 2 By satisfying this condition, the microporous membrane will relax early during the heat test, weakening the contractile force, and as a result, safety tends to be improved.

[0029] The tensile modulus of the polyolefin microporous membrane is preferably 120 N / cm or less, more preferably 100 N / cm or less, and even more preferably 90 N / cm or less in both MD and TD. A tensile modulus of 120 N / cm or less indicates that the membrane is not highly oriented as a separator for a lithium ion secondary battery, and in a heating test or the like, for example, when a blocking agent such as polyethylene melts and shrinks, the polyethylene etc. causes stress relaxation early, which suppresses the shrinkage of the separator in the battery and tends to easily prevent short circuits between electrodes (i.e., the safety of the separator during heating can be improved). Such a microporous membrane with a low tensile modulus can be easily achieved by including polyethylene having a weight average molecular weight of 500,000 or less in the polyolefin forming the microporous membrane. On the other hand, the lower limit of the tensile modulus of the microporous membrane is not particularly limited, but is preferably 10 N / cm or more, more preferably 30 N / cm or more, and even more preferably 50 N / cm or more. The tensile modulus of the microporous membrane can be appropriately adjusted by adjusting the degree of stretching and, if necessary, by relaxing after stretching.

[0030] The thickness of the polyolefin microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more, 4.0 μm or more. When the thickness of the microporous membrane is 1.0 μm or more, the membrane strength tends to be further improved. In addition, the thickness of the microporous membrane is preferably 24 μm or less, more preferably 22 μm or less, and even more preferably 20 μm or less, 18 μm or less. When the thickness of the microporous membrane is 24 μm or less, the ion permeability tends to be further improved. The thickness of the microporous membrane can be measured by the method described in the Examples.

[0031] [Heat-resistant B layer] The heat-resistant B layer is a heat-resistant layer laminated on at least one side of the base material A layer, and is preferably a heat-resistant porous layer having a large number of micropores therein from the viewpoint of the basic physical properties of the battery separator. In the heat-resistant porous layer, these micropores may have a structure in which they are connected to each other, and gas or liquid can pass from one side to the other side. From this viewpoint, the heat-resistant porous layer may be disposed on one or both sides of the base material A layer, and is preferably disposed so that at least a part of the base material A layer is exposed.

[0032] From the viewpoint of improving the heat resistance of the separator and the safety of the battery, the heat-resistant layer B preferably contains a heat-resistant resin and an inorganic filler. If desired, the heat-resistant layer B may also contain a thermoplastic polymer, any additive, and the like.

[0033] (Heat-resistant resin) In this embodiment, it is preferable to use, as the heat-resistant resin, a resin having a melting point of more than 150°C, a resin having a melting point of 250°C or more, or, for a resin that does not substantially have a melting point, a resin having a thermal decomposition temperature of 250°C or more. Examples of such heat-resistant resins include fully aromatic polyamides, polyimides, polyamideimides, polysulfones, polyethersulfones, polyketones, polyethers, polyetherketones, polyetherimides, cellulose; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose. Among them, fully aromatic polyamides (also called aramid resins) are preferred from the viewpoint of durability, and para-type aromatic polyamides and / or meta-type aromatic polyamides are more preferred. In addition, meta-type aromatic polyamides are preferred from the viewpoint of the formability of the porous layer and the oxidation-reduction resistance.

[0034] The heat-resistant resin has a molecular weight distribution Mw / Mn of 5≦Mw / Mn≦100 and / or a weight average molecular weight Mw of 8.0×10 3 Above 1.0×10 6It is preferable that the molecular weight is less than 1000 nm. When a heat-resistant resin characterized by these molecular weights is used, a better heat-resistant porous layer can be formed when a heat-resistant porous layer is formed on a polyolefin microporous membrane by a wet coating method. This is because a heat-resistant resin having a wide molecular weight distribution as described above also contains a large amount of low molecular weight substances, and the processability of the coating liquid in which the resin is dissolved is improved. Therefore, a heat-resistant porous layer with few defects and a uniform thickness is easily formed. In addition, since it becomes possible to perform coating well without applying a strong coating pressure, the occurrence of clogging of the pores on the surface of the polyolefin microporous membrane is suppressed, and the decrease in air permeability at the interface between the heat-resistant porous layer and the polyolefin microporous membrane is prevented. In addition, when the coating liquid is applied to the polyolefin microporous membrane and immersed in a coagulation liquid, the resin in the coating film becomes easy to move, and good pore formation is possible. Furthermore, the low molecular weight substances contained in the resin are compatible with the inorganic filler, and the drop-off of the inorganic filler that contributes to pore formation can be prevented. As a result, a heat-resistant porous layer having uniform fine pores can be easily formed, and therefore a separator having excellent ion permeability and good contact with the electrodes can be obtained.

[0035] The heat-resistant resin preferably contains 1% by weight to 15% by weight, more preferably 3% by weight to 10% by weight, of a low-molecular-weight polymer having a molecular weight of 8,000 or less. In this case, a good heat-resistant porous layer can be formed in the same manner as described above.

[0036] Furthermore, when aromatic polyamide is used as the heat-resistant resin, it is preferable that the terminal group concentration ratio of the aromatic polyamide is [COOX {wherein X represents hydrogen, an alkali metal or an alkaline earth metal}] / [NH2]≧1. For example, terminal carboxyl groups such as COONa have the effect of removing undesirable films formed on the negative electrode side of a battery. Therefore, when an aromatic polyamide having more terminal carboxyl groups than terminal amine groups is used, a non-aqueous electrolyte secondary battery with a stable discharge capacity over a long period of time tends to be obtained. For example, a battery having a good discharge capacity may be obtained even after 100 or 1000 charge / discharge cycles.

[0037] (thermoplastic resin) The heat-resistant layer B may contain a thermoplastic resin (excluding the heat-resistant resins described above). The heat-resistant layer B may contain, based on the total amount of the layer, preferably 60% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more of the thermoplastic resin.

[0038] Examples of the thermoplastic resin include the following: Polyolefin resins such as polyethylene, polypropylene, and α-polyolefin; Fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, or copolymers containing these; Diene-based polymers containing conjugated dienes such as butadiene and isoprene as monomer units, copolymers containing these, or hydrogenated products thereof; An acrylic polymer containing a (meth)acrylate, (meth)acrylic acid, or the like as a monomer unit and having no polyalkylene glycol unit, an acrylic polymer containing a (meth)acrylate, (meth)acrylic acid, or the like as a monomer unit and having one or two polyalkylene glycol units, or a copolymer containing these, or a hydrogenated product thereof; Rubbers such as ethylene propylene rubber, polyvinyl alcohol, and polyvinyl acetate; Polyalkylene glycols having no polymerizable functional groups, such as polyethylene glycol and polypropylene glycol; Resins such as polyphenylene ether, polyphenylene sulfide, and polyester; A copolymer having, as a copolymerization unit, an ethylenically unsaturated monomer having 3 or more repeating alkylene glycol units; and Combinations of these; Examples include: Among these, from the viewpoint of improving safety in a puncture test of a battery including the separator, it is preferable that the thermoplastic polymer contains a polymerized unit of a (meth)acrylic acid ester or (meth)acrylic acid.

[0039] From the viewpoint of improving safety in a puncture test of a battery equipped with the separator, the glass transition temperature (Tg) of the thermoplastic resin is preferably within the range of -40°C to 105°C, and more preferably within the range of -38°C to 100°C.

[0040] From the viewpoints of wettability to the base material A layer, adhesion between the base material A layer and the heat-resistant B layer, and contact with the separator electrodes, it is preferable that the heat-resistant B layer is blended with a polymer having a glass transition temperature of less than 20° C., and from the viewpoints of blocking resistance and ion permeability, it is preferable that the heat-resistant B layer is also blended with a polymer having a glass transition temperature of 20° C. or higher.

[0041] The thermoplastic resin having at least two glass transition temperatures can be achieved, without being limited thereto, by a method of blending two or more types of thermoplastic resins, a method of using a thermoplastic resin having a core-shell structure, or the like. The core-shell structure is a polymer having a double structure in which the polymer belonging to the central portion and the polymer belonging to the outer shell portion have different compositions. In particular, in polymer blends and core-shell structures, the glass transition temperature of the entire thermoplastic resin can be controlled by combining a polymer with a high glass transition temperature with a polymer with a low glass transition temperature, and multiple functions can be imparted to the entire thermoplastic resin.

[0042] In this embodiment, from the viewpoint of blocking suppression and ion permeability of the separator, it is preferable that the thermoplastic resin is particulate when the glass transition temperature is, for example, 20°C or higher, 25°C or higher, or 30°C or higher. By including a particulate thermoplastic copolymer in the heat-resistant B layer, the porosity of the heat-resistant B layer disposed on the substrate and the blocking resistance of the separator can be ensured.

[0043] The average particle size of the particulate thermoplastic copolymer is preferably 10 nm to 2,000 nm, more preferably 50 nm to 1,500 nm, even more preferably 100 nm to 1,000 nm, particularly preferably 130 nm to 800 nm, particularly preferably 150 to 800 nm, and most preferably 200 to 750 nm. The average particle size of 10 nm or more means that when the particulate thermoplastic polymer is applied to a substrate including at least a porous membrane, the dimensions of the particulate thermoplastic polymer are secured so that it does not enter the pores of the substrate. Therefore, in this case, it is preferable from the viewpoint of improving the contact between the electrode and the separator and the cycle characteristics of the battery. In addition, the average particle size of 2,000 nm or less is preferable from the viewpoint of applying a necessary amount of particulate thermoplastic resin to the substrate in order to achieve both the contact between the electrode and the separator and the cycle characteristics of the battery.

[0044] The particulate thermoplastic polymer described above can be produced by a known polymerization method using the corresponding monomer or comonomer. As the polymerization method, for example, a suitable method such as solution polymerization, emulsion polymerization, bulk polymerization, etc. can be adopted.

[0045] In this embodiment, since the heat-resistant B layer can be easily formed by coating, it is preferable to form a particulate thermoplastic polymer by emulsion polymerization and use the resulting thermoplastic polymer emulsion as the aqueous latex.

[0046] (Inorganic filler) The inorganic filler used in the heat-resistant layer B is not particularly limited, but is preferably one that has a melting point of 200° C. or higher, has high electrical insulation properties, and is electrochemically stable within the range of use of lithium ion secondary batteries.

[0047] Examples of the shape of the inorganic filler include granular, plate-like, scaly, needle-like, columnar, spherical, polyhedral, blocky, etc. A combination of inorganic fillers having these shapes may be used.

[0048] Average particle size of inorganic filler (D 50 ) is preferably 0.2 μm or more and 2.0 μm or less, and more preferably more than 0.2 μm and 1.2 μm or less. 50 Adjusting to within the above range is preferable from the viewpoint of suppressing thermal shrinkage at high temperatures (e.g., 150° C. or higher, 200° C. or higher, or 200° C. or higher) or improving bar impact fracture test properties at high temperatures, even when the heat-resistant porous layer has a thin thickness (e.g., 5 μm or less, or 4 μm or less). Examples of a method for adjusting the particle size and distribution of the inorganic filler include a method of reducing the particle size by pulverizing the inorganic filler using an appropriate pulverizing device such as a ball mill, a bead mill, or a jet mill.

[0049] In addition to the heat-resistant resin, the heat-resistant layer B preferably contains 25% by mass to 95% by mass of an inorganic filler based on the mass of the heat-resistant layer B. 25% by mass or more of the inorganic filler is preferred for dimensional stability and heat resistance at high temperatures, while 95% by mass or less of the inorganic filler is preferred for strength, handleability, or moldability.

[0050] Furthermore, from the viewpoint of improving battery safety at high temperatures in the event of an abnormality such as a fire, an unexpected internal short circuit in the battery, or a short circuit due to external destruction, the heat-resistant B layer preferably contains 30 mass % to 90 mass % and more preferably 32 mass % to 85 mass % of an inorganic filler having an average particle size in the range of 0.2 μm to 0.9 μm, based on the mass of the heat-resistant B layer.

[0051] The inorganic filler is not particularly limited, but examples thereof include oxide ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum oxide hydroxide, potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination.

[0052] Among these, from the viewpoint of improving the electrochemical stability and heat resistance of the separator, aluminum oxide compounds such as alumina and aluminum oxide hydroxide; and aluminum silicate compounds having no ion exchange capacity, such as kaolinite, dickite, nacrite, halloysite, and pyrophyllite, are preferred.

[0053] Alumina has many crystal forms, such as α-alumina, β-alumina, γ-alumina, and θ-alumina, and any of these can be suitably used. Among these, α-alumina is preferred because it is thermally and chemically stable.

[0054] As the aluminum oxide compound, aluminum oxide hydroxide (AlO(OH)) is particularly preferred. As the aluminum oxide hydroxide, boehmite is more preferred from the viewpoint of preventing internal short circuits caused by the generation of lithium dendrites. By employing particles mainly composed of boehmite as the inorganic filler constituting the heat-resistant B layer, a very lightweight porous layer can be realized while maintaining high permeability, and even in a thinner porous layer, the thermal shrinkage of the microporous film at high temperatures is suppressed, tending to exhibit excellent heat resistance. Synthetic boehmite is even more preferred, which can reduce ionic impurities that adversely affect the characteristics of electrochemical devices.

[0055] As the aluminum silicate compound having no ion exchange capacity, kaolin, which is mainly composed of kaolin mineral, is more preferable because it is inexpensive and easily available. Kaolin includes wet kaolin and calcined kaolin obtained by calcining wet kaolin. In this embodiment, calcined kaolin is particularly preferable. Calcined kaolin is particularly preferable from the viewpoint of electrochemical stability because water of crystallization is released during the calcination process and impurities are also removed.

[0056] The porosity of the heat-resistant B layer is preferably in the range of 60% to 90%. When the porosity of the heat-resistant porous layer is 90% or less, it is preferable from the viewpoint of heat resistance. Also, when the porosity of the heat-resistant B layer is 60% or more, it is preferable from the viewpoint of cycle characteristics or storage characteristics and discharge characteristics of the battery. From the same viewpoint, the coating amount (basis weight) of the heat-resistant B layer is 2 g / m 2 ~10g / m 2 It is preferable that:

[0057] (optional ingredient) The heat-resistant B layer in this embodiment may contain optional components other than the heat-resistant resin, thermoplastic resin, and inorganic filler. Examples of the optional components include known additives (excluding inorganic particles) described above for the base A layer and the polyolefin microporous membrane, and resins other than the heat-resistant resin and thermoplastic resin.

[0058] From the viewpoints of the cycle performance and nail penetration test safety of the battery, it is preferable that the heat-resistant B layer contains at least one selected from the group consisting of ceramics, aramid resin, and polyvinylidene fluoride (PVDF) among the components described above.

[0059] (Characteristics of heat-resistant layer B) In this embodiment, the area ratio of the heat-resistant B layer to the total area on the surface of the base material A layer where the heat-resistant B layer can be arranged is preferably 5% to 90%. Setting this area ratio to 90% or less is preferable from the viewpoint of further suppressing the blocking of the pores of the base material by the heat-resistant resin and further improving the permeability of the separator. On the other hand, setting this area ratio to 5% or more is preferable from the viewpoint of further improving the adhesion to the electrode. From this viewpoint, the upper limit of the area ratio of the heat-resistant B layer is more preferably 80% or less, 75% or less, or 70%, and the lower limit of this area ratio is more preferably 10% or more, or 15% or more. This area ratio is measured by observing the surface of the obtained separator on which the heat-resistant B layer is formed by SEM. In addition, when the heat-resistant B layer is a layer in which inorganic particles are mixed, the area of ​​the contained resin is calculated by assuming the total area of ​​the contained resin and inorganic particles to be 100%.

[0060] When the heat-resistant B layer is disposed on only a part of the surface of the base material A layer, the arrangement pattern of the heat-resistant B layer may be, for example, a dot pattern, a stripe pattern, a lattice pattern, a striped pattern, a tortoiseshell pattern, a random pattern, or a combination thereof. From the viewpoints of the heat resistance and insulating properties of the separator and the high-temperature safety of the battery, the thickness of the heat-resistant B layer disposed on the base material A layer is preferably 0.01 μm to 7 μm, more preferably 0.1 μm to 6.5 μm, and even more preferably 1 to 6 μm per side of the base material A layer.

[0061] [Silane crosslinking reaction] The battery separator preferably contains a silane-modified polyolefin, and more preferably, the silane-modified polyolefin is contained in the substrate A layer (i.e., the polyolefin microporous film) of the battery separator.

[0062] It is preferable that the battery separator containing the silane-modified polyolefin initiates a silane crosslinking reaction of the silane-modified polyolefin when it comes into contact with an electrolyte. Examples of the silane-modified polyolefin include silane-grafted polyethylene and silane-grafted polypropylene. It is considered that the functional group contained in the polyolefin constituting the separator is not incorporated into the crystalline part of the polyolefin, but is crosslinked in the amorphous part. Therefore, when the separator according to the present embodiment comes into contact with an electrolyte, it forms a crosslinked structure using chemical substances in the electrolyte, thereby suppressing the increase in internal stress or the deformation of the produced battery, thereby improving safety in nail penetration tests and the like.

[0063] When the silane-modified polyolefin is contained in the base material A layer (i.e., the polyolefin microporous membrane), the base material A layer may contain (A) silane-grafted polyethylene, (B) silane-grafted polypropylene, (C) polyethylene (a polyethylene different from the above-mentioned silane-grafted polyethylene: hereinafter, also simply referred to as "polyethylene"), etc. The polyolefin microporous membrane containing the components (A) to (C) tends to have a membrane rupture temperature of 170°C to 230°C as measured by thermomechanical analysis (TMA) as the crosslinking reaction progresses. Furthermore, based on a total of 100% by mass of the silane-grafted polyethylene, the silane-grafted polypropylene, the polyethylene, and the optional component (D) (one or more kinds), the content of the silane-grafted polyethylene is 2 to 50% by mass, the content of the silane-grafted polypropylene is 1 to 40% by mass, the content of the polyethylene is 5 to 95% by mass, and the content of the optional components is 0 to 10% by mass. This makes it possible to realize a separator with high quality (e.g., less resin aggregates in the separator), and by including such a separator, it is possible to ensure high safety of the battery (improved pass rate of safety test evaluated by nail penetration test).

[0064] The optional components include components different from any of (A) to (C), such as at least one of a polymer different from any of (A) to (C) or an additive described below. The optional components are not limited to a single type. The separator may contain multiple types of polymers different from any of (A) to (C), may contain multiple types of additives, or may contain both the polymer and the additive. When the separator contains multiple types of optional components, the total content of the multiple types of optional components may be 10 mass% or less.

[0065] In this regard, in the microporous membrane, a silane crosslinked structure (gelation structure) is constructed by the silane graft modified polyethylene and the silane graft modified polypropylene, and high temperature membrane rupture resistance can be exhibited. This is presumably because polypropylenes, polyethylenes, and / or polypropylene and polyethylene dispersed in the mixed resin are suitably linked by the silane crosslinked structure. That is, it is considered that polypropylenes crosslink with each other, and the polypropylene and polyethylene crosslink with each other in a compatible manner to form a contact layer between them. In this case, the polypropylene becomes the core part, and the contact layer around the core part becomes the shell part, forming a core-shell structure, and such a core-shell structure is dispersed in the polyethylene. Furthermore, crosslinking between polyethylenes also occurs, and the morphology of the entire microporous membrane changes, and it is considered that the membrane shape can be maintained even when the melting point of the polyethylene (for example, about 130°C to 140°C) is exceeded and the melting point of the polypropylene (for example, about 170°C) is near or exceeded. In addition, the change in the morphology of the microporous membrane as a whole also improves the tensile elongation, which is expected to reduce the possibility of the separator breaking when the battery is deformed by an external force.

[0066] From the viewpoint of ensuring high-temperature membrane rupture resistance and improving tensile elongation, the content of the silane-grafted modified polyethylene is preferably 3 mass% or more, more preferably 4 mass% or more, and is preferably 49.5 mass% or less, more preferably 49 mass% or less, based on 100 mass% in total of the above components (A) to (D). From the same viewpoint as above, the content ratio of the silane-grafted modified polypropylene is preferably 1.5% by mass or more, more preferably 2% by mass or more, and preferably 39.5% by mass or less, more preferably 39% by mass or less, based on the total of 100% by mass. Furthermore, from the same viewpoint as above, the content of polyethylene (other than the above-mentioned silane-grafted modified polyethylene) is preferably 10 mass% or more, more preferably 12 mass% or more, and is preferably 94.5 mass% or less, more preferably 94 mass% or less, based on the above total of 100 mass%.

[0067] The microporous membrane may contain known additives such as organometallic catalysts (dehydration condensation catalysts); plasticizers; metal soaps such as calcium stearate or zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; and color pigments.

[0068] ((A) Silane-grafted polyethylene, and (B) Silane-grafted polypropylene) The silane-grafted polyethylene has a polyethylene main chain to which an alkoxysilyl group is grafted, while the silane-grafted polypropylene has a polypropylene main chain to which an alkoxysilyl group is grafted.

[0069] In both the silane-grafted polyethylene and the silane-grafted polypropylene, it is presumed that the alkoxysilyl group is converted to a silanol group through a hydrolysis reaction with water, and then undergoes a crosslinking reaction to form a siloxane bond (see the formula below; the ratio of the structure T0 to the structure T1, T2, or T3 is arbitrary). The alkoxide substituted on the alkoxysilyl group is not particularly limited, but examples thereof include methoxide, ethoxide, butoxide, etc. For example, in the formula below, R is methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc. [ka]

[0070] In both the silane-grafted polyethylene and the silane-grafted polypropylene, the main chain and the graft are connected by a covalent bond in the silane-grafted polypropylene. The structure forming such a covalent bond is not particularly limited, but may be, for example, an alkyl, an ether, a glycol, or an ester. In both the silane-grafted polyethylene and the silane-grafted polypropylene, the graft ratio is preferably 2.0 mol% or less, more preferably 1.7 mol% or less, in terms of vinyl silanol units, relative to the ethylene unit, at the stage before the crosslinking reaction.

[0071] Both the silane-grafted modified polyethylene and the silane-grafted modified polypropylene preferably have an average viscosity molecular weight (Mv) of 20,000 to 150,000 and a density of 0.90 to 0.97 g / cm 3 The melt flow rate (MFR) of the silane-grafted modified polyethylene at 190°C and the MFR of the silane-grafted modified polypropylene at 230°C are 0.1 to 15 g / min.

[0072] The polyethylene constituting the silane-grafted modified polyethylene may be composed of one type of ethylene alone, or may be composed of two or more types of ethylene. Two or more types of silane-grafted modified polyethylene composed of different ethylenes may be used in combination.

[0073] In this embodiment, in order to achieve both the construction of a pore structure that exhibits low ion resistance in the normal battery use temperature range and the expression of a high impedance value after the separator is melted (up to 250°C), the base material A layer has been found to have a preferred resin raw material composition by focusing on the porous structure obtained by melt-kneading the polyethylene raw material, silane-modified polyolefin, and plasticizer in an extruder, followed by thermally induced phase separation. In the raw material composition, it is preferable to use a total of three types of polyethylene with an average viscosity molecular weight (Mv) of 2,000,000 to 9,000,000, an average viscosity molecular weight (Mv) of 500,000 to 2,000,000, and a silane-modified polyolefin with an average viscosity molecular weight (Mv) of 20,000 to 150,000. It is more preferable to adjust the ratio of these resins depending on the average viscosity molecular weight of the polyethylene and silane-modified polyolefin used. In the above raw material composition, the silane-modified polyolefin having an average viscosity molecular weight (Mv) of 20,000 to 150,000 accounts for 5% by mass to 60% by mass of the total, and the ratio of polyethylene having an average viscosity molecular weight (Mv) of 2,000,000 to 9,000,000:polyethylene having an average viscosity molecular weight (Mv) of 500,000 to 2,000,000 contained therein is preferably 8:2 to 0.5:9.5.

[0074] The polypropylene constituting the silane-grafted modified polypropylene may be composed of one type of propylene alone, or may be composed of two or more types of propylene. Two or more types of silane-grafted modified polypropylenes composed of different propylenes may be used in combination.

[0075] The polypropylene constituting the silane-grafted modified polypropylene is preferably a propylene homopolymer. Considering the manufacturing process of the separator according to this embodiment, the silane-grafted modified polypropylene has a modification amount of 10% or less, preferably 5% or less, and more preferably 2% or less of all propylene units in the main chain before the crosslinking treatment step described later. A preferred silane-grafted modified polypropylene has a density of 0.90 to 0.96 g / cm 3 and the melt flow rate (MFR) at 190° C. is 0.2 to 5 g / min.

[0076] The crosslinking reaction is accelerated by using an organometallic catalyst. In this specification, a resin containing silane-grafted modified polypropylene to which an organometallic catalyst is added beforehand, prior to the sheet forming process (for example, at the stage of a kneading process that is performed as required), is referred to as a masterbatch resin.

[0077] [Manufacturing method of battery separator] (Method of manufacturing polyolefin microporous membrane) The method for producing a battery separator will be described below with reference to the case where the polyolefin microporous membrane is a single-layer membrane (flat membrane), but is not intended to exclude forms other than the flat membrane. The method for producing a microporous membrane according to this embodiment includes the following steps: (1) Sheet forming process; (2) Stretching process; (3) a porous body forming step; and (4) Heat treatment process; The method for producing a microporous membrane according to this embodiment may optionally include a resin modification step or kneading step before the sheet forming step (1), and / or a winding and slitting step after the heat treatment step (3), but preferably does not include a crosslinked structure formation step or a contact step with a crosslinking-promoting catalyst from the viewpoint of maintaining the crosslinking property of the microporous membrane until it is installed in a battery.

[0078] The crosslinked structure forming step includes (1) a sub-step of condensing multiple functional groups contained in the microporous membrane, (2) a sub-step of reacting functional groups contained in the microporous membrane with chemicals inside the battery, or (3) a sub-step of reacting functional groups contained in the microporous membrane with other functional groups. The crosslinking-promoting catalyst is any catalyst capable of promoting a crosslinking reaction, such as the above-described (I) condensation reaction of multiple identical functional groups, (II) reaction between multiple different functional groups, (III) chain condensation reaction between functional groups and an electrolyte, and (IV) chain condensation reaction between functional groups and an additive.

[0079] In the kneading step, for example, a polyolefin, and optionally other resins, and a plasticizer or inorganic material can be kneaded using a kneader. From the viewpoint of suppressing the generation of resin aggregates in the production process and maintaining the crosslinking property of the microporous membrane until it is housed in a battery, it is preferable not to add a masterbatch resin containing a crosslinking-promoting catalyst to the kneaded mixture.

[0080] The polyolefin subjected to the kneading step or the sheet forming step (1) is not limited to an olefin homopolymer, but may be a polyolefin copolymerized with a monomer having a functional group, or a functional group-modified polyolefin. The functional group is a functional group capable of participating in the formation of a crosslinked structure, and may be, for example, the functional groups A and / or B in the reactions (I) to (V) described above. By preparing a polyolefin raw material containing a monomer unit having the functional groups A and / or B in advance, the resin modification step can be omitted.

[0081] On the other hand, if the polyolefin raw material does not have a functional group capable of participating in the formation of a crosslinked structure or the molar fraction of such a functional group is less than a predetermined ratio, the polyolefin raw material can be subjected to a resin modification process to incorporate a functional group into the resin backbone or increase the molar fraction of the functional group to obtain a functional group-modified polyolefin. The resin modification process can be carried out by a known method. For example, the polyolefin raw material can be contacted with a reaction reagent by liquid spraying, gas spraying, dry mixing, immersion, coating, etc., so that the functional groups A and / or B can be introduced into the polyolefin backbone.

[0082] The plasticizer is not particularly limited, but examples thereof include organic compounds that can form a uniform solution with polyolefin at a temperature below the boiling point. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decyl alcohol, nonyl alcohol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. are included. Among these, paraffin oil and dioctyl phthalate are preferred. The plasticizer may be used alone or in combination of two or more. The ratio of the plasticizer is not particularly limited, but from the viewpoint of the porosity of the obtained microporous film, the polyolefin and the silane-grafted modified polyolefin are preferably 20% by mass or more based on the total mass as necessary, and from the viewpoint of the viscosity during melt kneading, it is preferably 90% by mass or less.

[0083] The sheet forming step (1) is a step of extruding the obtained kneaded product or a mixture of polyolefin and plasticizer, cooling and solidifying it, and forming and processing it into a sheet to obtain a sheet. The method of forming the sheet is not particularly limited, but for example, a method of compressing and cooling the molten product extruded after melt kneading to solidify it is included. The cooling method includes a method of directly contacting the product with a cooling medium such as cold air or cooling water, a method of contacting the product with a roll or press cooled with a refrigerant, etc., and the method of contacting the product with a roll or press cooled with a refrigerant is preferred in terms of excellent film thickness controllability.

[0084] When a polyolefin copolymerized with a monomer having a functional group or a functional group-modified polyolefin is used in combination with another polyolefin, from the viewpoint of resin aggregates or maximum internal heat generation rate in the separator, the mass ratio (polyolefin copolymerized with a monomer having a functional group or a functional group-modified polyolefin / other polyolefin) in the sheet molding step is preferably 0.05-0.4 / 0.6-0.95, and more preferably 0.06-0.38 / 0.62-0.94.

[0085] From the viewpoint of improving safety by suppressing thermal runaway upon battery destruction while having low-temperature shutdown properties of 150°C or less and resistance to membrane rupture at high temperatures of 180 to 230°C, it is preferable that in the sheet molding process, the polyolefin copolymerized with a monomer having a functional group or the functional group-modified polyolefin is not a masterbatch resin that contains a catalyst that promotes the crosslinking reaction of the functional group before the sheet molding process.

[0086] The stretching step (2) is a step of extracting a plasticizer or an inorganic material from the obtained sheet as necessary, and further stretching the sheet in at least one axial direction. Examples of the sheet stretching method include MD uniaxial stretching by a roll stretching machine, TD uniaxial stretching by a tenter, sequential biaxial stretching by a combination of a roll stretching machine and a tenter or a tenter and a tenter, and simultaneous biaxial stretching by a simultaneous biaxial tenter or inflation molding. From the viewpoint of obtaining a more uniform film, simultaneous biaxial stretching is preferable. The total areal magnification is preferably 8 times or more, more preferably 15 times or more, and even more preferably 20 times or more or 30 times or more, from the viewpoint of the uniformity of the film thickness, the balance between the tensile elongation, the porosity, and the average pore size. By having a total areal magnification of 8 times or more, it tends to be easy to obtain a film with high strength and good thickness distribution. In addition, from the viewpoint of preventing breakage, this areal magnification may be 250 times or less.

[0087] The porous body forming step (3) is a step of extracting the plasticizer from the stretched product after the stretching step to make the stretched product porous. The method of extracting the plasticizer is not particularly limited, but examples thereof include a method of immersing the stretched product in an extraction solvent and a method of showering the stretched product with the extraction solvent. The extraction solvent is not particularly limited, but for example, it is preferably a poor solvent for polyolefin and a good solvent for plasticizers or inorganic materials, and has a boiling point lower than the melting point of polyolefin. Such an extraction solvent is not particularly limited, but examples thereof include hydrocarbons such as n-hexane or cyclohexane; halogenated hydrocarbons such as methylene chloride or 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol or isopropanol; ketones such as acetone or 2-butanone; and alkaline water. The extraction solvent may be used alone or in combination of two or more types.

[0088] The heat treatment step (4) is a step of extracting a plasticizer from the sheet as necessary after the stretching step, and further performing heat treatment to obtain a microporous membrane. The heat treatment method is not particularly limited, but examples include a heat setting method in which stretching and relaxation operations are performed using a tenter or roll stretching machine. The relaxation operation refers to a reduction operation performed at a predetermined temperature and relaxation rate in the machine direction (MD) and / or transverse direction (TD) of the membrane. The relaxation rate refers to the value obtained by dividing the MD dimension of the membrane after the relaxation operation by the MD dimension of the membrane before the operation, or the value obtained by dividing the TD dimension of the membrane after the relaxation operation by the TD dimension of the membrane before the operation, or when both MD and TD are relaxed, the value obtained by multiplying the relaxation rate of MD and the relaxation rate of TD.

[0089] [Winding / Slitting process / Post-processing process] The winding step is a step in which the obtained microporous membrane is slit, if necessary, and wound around a predetermined core.

[0090] It is preferable to subject the obtained polyolefin microporous membrane to a surface treatment, since this makes it easier to apply a coating liquid thereafter and improves the adhesion between the polyolefin microporous membrane as the substrate A layer and the heat-resistant layer B. Examples of the surface treatment method include a corona discharge treatment method, a plasma treatment method, a mechanical roughening method, a solvent treatment method, an acid treatment method, and an ultraviolet oxidation method.

[0091] (Multi-layered substrate) As an example of the method for producing a multi-layer microporous polyolefin film, the production of a multi-layer film having a first microporous layer, a second microporous layer, and a first microporous layer in this order is described below. As a method for laminating these porous layers, for example, the following three-layer simultaneous lamination method can be mentioned: The polyolefin resin composition and the plasticizer, which are the components of the first and second microporous layers, are melt-kneaded separately using a twin-screw extruder to form an olefin solution, and then each polyolefin solution is fed from each twin-screw extruder to a three-layer T-die, and the layer thickness ratio of each layer (first polyolefin solution layer / second polyolefin solution layer / first polyolefin solution layer) formed from each solution is adjusted to a desired range, and the layer is cooled while being taken up at a predetermined take-up speed to form a gel-like three-layer sheet. In the above, a three-layer T-die is used to simultaneously laminate and form three layers, but each layer may be formed separately and then combined into three layers.

[0092] (How to arrange heat-resistant layer B) The composition for forming the heat-resistant B layer can be disposed on the substrate by, for example, applying a coating liquid containing a heat-resistant resin and / or a thermoplastic resin to the substrate. The heat-resistant resin and / or the thermoplastic resin may be synthesized by emulsion polymerization, and the resulting emulsion may be used as it is as the coating liquid. The coating liquid preferably contains a poor solvent such as water or a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol).

[0093] The method of applying the coating liquid containing a heat-resistant resin and / or a thermoplastic resin onto the substrate of a polyolefin microporous membrane is not particularly limited as long as it can realize the desired coating pattern, coating thickness, and coating area. For example, the coating method described above for applying the inorganic particle-containing coating liquid may be used. From the viewpoint of having a high degree of freedom in the coating shape of the composition for forming the heat-resistant B layer and being able to easily adjust the preferred area ratio of the heat-resistant B layer as described above, the gravure coater method or the spray coating method is preferred.

[0094] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the base material A layer and the heat-resistant layer B. For example, there are a method of drying the base material A layer at a temperature below its melting point while fixing it, a method of drying under reduced pressure at a low temperature, a method of immersing in a poor solvent for the heat-resistant resin and / or thermoplastic resin to solidify the heat-resistant resin and / or thermoplastic resin into particles and simultaneously extracting the solvent, and the like.

[0095] The separator obtained by the method including the various steps described above can be used in a nonaqueous electrolyte secondary battery including a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a nonaqueous electrolyte solution obtained by dissolving an electrolyte in a nonaqueous solvent, and can be preferably used in a lithium secondary battery or a lithium ion secondary battery.

[0096] [Battery assembly kit] In another embodiment of the present invention, a battery assembly kit is provided that includes the battery separator described above. The battery assembly kit includes two components: (1) an exterior housing housing a laminate or wound body of a positive electrode, a negative electrode, and a battery separator as described above; and (2) a container containing a nonaqueous electrolyte; When using the battery assembly kit, a cross-linked structure is formed in the separator by contacting the separator in element (1) with the non-aqueous electrolyte in element (2) and contacting the non-aqueous electrolyte with the laminate or wound body inside the exterior body, and / or by continuing the charge / discharge cycle of the assembled battery, thereby forming a battery that is both safe and has a high output.

[0097] Without wishing to be bound by theory, it is believed that when the electrolyte or electrolyte solution comes into contact with the electrodes and / or when the battery is charged and discharged, a substance that catalyzes the crosslinking reaction or a substance having a functional group that becomes part of the crosslinked structure is present in the electrolyte solution, on the inner surface of the exterior body, or on the surface of the electrodes, and dissolves in the electrolyte solution and uniformly swells and diffuses into the amorphous part of the polyolefin, thereby uniformly promoting the crosslinking reaction of the separator-containing laminate or wound body. The substance that catalyzes the crosslinking reaction may be in the form of an acid solution or film, and when the electrolyte contains lithium hexafluorophosphate (LiPF6), it may be hydrogen fluoride (HF) or a fluorine-containing organic substance derived from hydrogen fluoride (HF). The substance having a functional group that becomes part of the crosslinked structure may be, for example, a compound having the functional groups A and / or B described above, the electrolyte solution itself, various additives, etc.

[0098] The positive and negative electrodes may have lead terminals attached or formed in advance. From the viewpoint of use of the assembly kit and charge / discharge of the assembled battery, it is preferable that the lead terminals are welded to the exposed parts of the positive and negative electrode current collectors after laminating the positive and negative electrodes and the separator and before placing the laminate or wound body in an outer casing (more preferably before pouring the electrolyte).

[0099] (Non-aqueous electrolyte) From the viewpoint of promoting the cross-linking reaction of the separator, the nonaqueous electrolyte stored in element (2) is preferably a fluorine (F)-containing lithium salt such as LiPF6 that generates HF, or an electrolyte having an unshared electron pair such as LiN(SO2CF3)2 or LiSO3CF3, or alternatively LiBF4, LiBC4O8 (LiBOB), etc.

[0100] (Separator) In the laminate or wound body contained in element (1) of the battery assembly kit, the battery separator is more preferably disposed between the positive and negative electrodes.

[0101] When the battery separator contains a silane-modified polyolefin, the nonaqueous electrolyte stored in element (2) is preferably an electrolyte containing fluorine (F) such as LiPF6 that generates HF, or an electrolyte having an unshared electron pair such as LiN(SO2CF3)2 or LiSO3CF3, from the viewpoint of promoting the crosslinking reaction of the separator. LiBF4, LiBC4O8 (LiBOB), etc. can also be used.

[0102] (accessories) In order to promote the crosslinking reaction of the separator, the battery assembly kit may include, as an accessory (or element (C)), a separate container for accommodating a catalyst for promoting the crosslinking reaction, such as a mixture of an organometallic catalyst and water, an acid solution, a base solution, or the like.

[0103] [Nonaqueous electrolyte secondary battery] The separator according to the present embodiment can be used in a non-aqueous electrolyte secondary battery comprising a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a non-aqueous electrolyte solution obtained by dissolving an electrolyte in a non-aqueous solvent. The non-aqueous electrolyte secondary battery can include a positive electrode, a negative electrode, a separator, a non-aqueous electrolyte solution, an additive, a battery exterior body, etc. The separator according to the present embodiment is preferably disposed between the positive and negative electrodes, and the non-aqueous electrolyte solution may include an additive as desired.

[0104] When a battery separator contains a silane-modified polyolefin, when the separator is housed in a battery outer casing, the silane-modified polyolefin reacts with chemicals contained in the electrolyte or additives to form a crosslinked structure, and the separator produced in the battery has a crosslinked structure.

[0105] As the positive electrode, a known battery positive electrode can be used, and from the viewpoint of the effect of the present invention, a positive electrode that is easily thermally decomposed or releases O2 can also be used. In addition, a composite positive electrode of lithium and another metal can be used, and a composite positive electrode of at least one metal selected from the group consisting of nickel, manganese, and cobalt and lithium, such as an LNO positive electrode, an NCA positive electrode, an LCO positive electrode, a nickel-manganese-cobalt (NMC)-based lithium-containing positive electrode, etc. can also be used. In this embodiment, an NMC positive electrode having a relatively high nickel content can also be preferably used, and it is more preferable that the molar ratio of the amount of nickel (Ni) to the total amount of nickel, manganese, and cobalt of the positive electrode is 3 to 9, 5 to 9, 6 to 9, 5 to 8, or 6 to 8.

[0106] The electrolyte contained in the battery is as explained in the above [Battery Assembly Kit].

[0107] The additives contained in the battery may be, for example, a dehydration condensation catalyst, metal soaps such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, a coloring pigment, and the like.

[0108] Specific examples of the non-aqueous electrolyte secondary battery include a lithium secondary battery, a lithium ion secondary battery, a lithium ion capacitor, etc. Among these, from the viewpoint of practicality, a lithium secondary battery, a lithium ion secondary battery, or a lithium ion capacitor is preferred, and a lithium secondary battery or a lithium ion secondary battery is more preferred.

[0109] [Lithium-ion secondary battery] A lithium ion secondary battery (LIB) is a storage battery using a lithium-containing positive electrode, a negative electrode, and an electrolyte solution containing an organic solvent containing a lithium salt such as LiPF6. As the positive electrode, a known LIB positive electrode can be used, and from the viewpoint of the effects of the present invention, a positive electrode that is easily thermally decomposed or releases O2 can also be used, and a lithium composite metal oxide positive electrode, for example, an LNO positive electrode, an NCA positive electrode, an LCO positive electrode, an NMC-based positive electrode, etc. can be used. As the negative electrode, a carbon material such as natural graphite, artificial graphite, hard carbon, Si-based material, etc. can be used. The electrolyte solution described above for the battery assembly kit may also be used for the lithium ion secondary battery. For example, for an NMC-based positive electrode, from the viewpoint of the effects of the present invention, it is preferable that the molar ratio of the Ni amount to the total amount of NMC in the positive electrode is 4 to 9, 5 to 9, 6 to 9, 5 to 8, or 6 to 8.

[0110] When a lithium-ion secondary battery is charged or discharged, ionized lithium travels back and forth between the positive and negative electrodes. In order to prevent short circuits between the positive and negative electrodes and to ensure that the ionized lithium travels between the positive and negative electrodes at a relatively high speed, a separator is placed between the positive and negative electrodes.

[0111] [Battery manufacturing method] A battery can be produced by stacking or winding a positive electrode, a negative electrode and a separator, housing them in an exterior body, pouring an electrolyte into the exterior body, and sealing the exterior body.

[0112] In addition, the battery assembly kit described above can be used in a battery manufacturing method. In that case, the battery manufacturing method includes the following steps: (A) preparing the battery assembly kit described above; (a) combining element (1) and element (2) of a battery assembly kit and contacting the laminate or wound body of the positive electrode, negative electrode, and separator with an electrolyte; (c) optionally performing at least one charge / discharge cycle; may include.

[0113] The steps (a) to (c) can be performed by a method known in the art, except for using the battery separator and non-aqueous electrolyte according to the present embodiment, and a positive electrode, a negative electrode, an exterior body, and a charge / discharge device known in the art can be used. When the battery separator according to the present embodiment contains a silane-modified polyolefin, a crosslinked structure is formed when the separator is housed in a battery, so that the battery separator can be adapted to a conventional battery manufacturing process and can cause a crosslinking reaction after the battery is manufactured to improve safety in nail penetration tests and the like.

[0114] The nonaqueous electrolyte battery, particularly the LIB, manufactured as described above includes the separator according to this embodiment, and therefore the performance (e.g., cycle performance, safety evaluated by a nail penetration test) can be further improved.

[0115] The various physical properties, measured values ​​and parameters described above can be measured by the methods described in the Examples below, unless otherwise specified. EXAMPLES

[0116] Next, the present embodiment will be described in more detail with reference to examples and comparative examples, but the present embodiment is not limited to the following examples as long as it does not depart from the gist of the present embodiment. Note that the physical properties in the examples were measured by the following methods.

[0117] (Method for detecting silane-modified polyolefin contained in separator) In the crosslinked state, the silane-modified polyolefin contained in the separator is insoluble or has insufficient solubility in organic solvents, so that it may be difficult to measure the content of the silane-modified polyolefin directly from the separator. In this case, as a pretreatment of the sample, methyl orthoformate, which does not cause side reactions, is used to decompose the siloxane bond into methoxysilanol, and then a solution NMR measurement is performed to detect the silane-modified polyolefin contained in the separator or to perform a GPC measurement. The pretreatment experiment can be performed with reference to Japanese Patent No. 3529854 and Japanese Patent No. 3529858.

[0118] Specifically, the silane-modified polyolefin used as a raw material in the manufacture of separators 1 H or 13 The C NMR identification can be used to detect silane-modified polyolefins contained in separators. 1 H and 13 An example of a C NMR measurement technique is described below.

[0119] ( 1 H NMR measurement) The sample was dissolved in o-dichlorobenzene-d4 at 140°C, and the proton resonance frequency was 600 MHz. 1 Obtain H-NMR spectra. 1 The H-NMR measurement conditions are as follows. Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 1sec Number of times: 1000 or more Sample concentration: 1 wt / vol%

[0120] ( 13 C NMR measurement) The sample was dissolved in o-dichlorobenzene-d4 at 140°C. 13Obtain a C-NMR spectrum. 13 The measurement conditions for C-NMR are as follows: Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 5sec Accumulation count: 10,000 times or more Sample concentration: 10 wt / vol%

[0121] 1 H and / or 13 By measuring C NMR, it is possible to confirm the amount of silane unit modification in the silane-modified polyolefin and the amount of alkyl group modification in the polyolefin in the polyolefin raw material, and to identify the content of silane-modified polyolefin in the separator (-CH2-Si: 1 H, 0.69 ppm, t; 13 C, 6.11 ppm, s) is possible.

[0122] (1) Weight average molecular weight A calibration curve was created by measuring standard polystyrene under the following conditions using a Waters ALC / GPC 150C (trademark). Chromatograms were also measured under the same conditions for each of the following polymers, and the weight-average molecular weight of each polymer was calculated based on the calibration curve by the following method. Column: Tosoh GMH6-HT (trademark) x 2 + GMH6-HTL (trademark) x 2 Mobile phase: o-dichlorobenzene Detector: Differential refractometer Flow rate: 1.0ml / min Column temperature: 140℃ Sample concentration: 0.1wt% (Weight-average molecular weight and number-average molecular weight of polyethylene, polypropylene and silane-grafted polyolefin) Each molecular weight component in the obtained calibration curve was multiplied by 0.43 (Q factor of polyethylene / Q factor of polystyrene = 17.7 / 41.3) or 0.64 (Q factor of polypropylene / Q factor of polystyrene = 26.4 / 41.3) to obtain a molecular weight distribution curve converted into polyethylene or polypropylene, and the weight average molecular weight and number average molecular weight were calculated. Note that the same Q factor as polyethylene was used for silane-grafted polyethylene, and the same Q factor as polypropylene was used for silane-grafted polypropylene. (Weight average molecular weight of resin composition) The weight average molecular weight was calculated using the Q factor value of the polyolefin with the largest mass fraction, and otherwise in the same manner as in the case of polyethylene.

[0123] (2) Viscosity average molecular weight (Mv) The intrinsic viscosity [η] in decalin solvent at 135°C was determined based on ASTM-D4020. The Mv of polyethylene and silane-modified polyethylene was calculated using the following formula. [η]=6.77×10 -4 Mv 0.67

[0124] (3) Melt mass flow rate (MFR) (g / 10 min) Using a melt mass flow rate measuring instrument (Melt Indexer F-F01) manufactured by Toyo Seiki, the weight of the resin extruded in 10 minutes at 190°C and a load of 2.16 kg was determined as the MFR value for polyethylene and silane-modified polyethylene. The MFR value for polypropylene and silane-modified polypropylene was measured at 230°C.

[0125] (4) Film thickness (μm) The thickness of the microporous membrane was measured using a micro thickness gauge (KBM (trademark)) manufactured by Toyo Seiki Seisakusho Co., Ltd.) at room temperature of 23±2° C. and a relative humidity of 60%. Specifically, the thickness was measured at five points at approximately equal intervals across the entire width in the TD direction, and the average value was obtained.

[0126] (5) Porosity (%) A 10 cm x 10 cm square sample was cut from the microporous membrane and its volume (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) and the porosity was calculated using the following formula: The density of the mixed composition was determined by calculating the density of each of the raw materials used and the mixing ratio. Porosity (%) = (volume-mass / density of mixed composition) / volume x 100

[0127] (6) Air permeability (sec / 100cm 3 ) In accordance with JIS P-8117 (2009), Gurley air permeability tester manufactured by Toyo Seiki Co., Ltd. The air permeability of the samples was measured using a meter, G-B2 (trademark).

[0128] (7) Impedance (Ω cm 2 ) <<Preparation of the positive electrode>> LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2, carbon black as a conductive assistant, and polyvinylidene fluoride solution as a binder were mixed in a solid content mass ratio of 91:5:4, and N-methyl-2-pyrrolidone was added as a dispersion solvent so that the solid content was 68 mass%, and further mixed to prepare a slurry solution. This slurry solution was applied to one side of an aluminum foil with a thickness of 15 μm so that part of the aluminum foil was exposed, and then the solvent was dried and removed to obtain a coating amount of 175 g / m2. 2 Furthermore, the density of the positive electrode mixture was 2.8 g / cm 3 The coated area was then cut to a size of 30 mm×50 mm and to include an exposed portion of the aluminum foil, and an aluminum lead piece was welded to the exposed portion of the aluminum foil to obtain a positive electrode.

[0129] <<Preparation of the negative electrode>> Artificial graphite was mixed as the negative electrode active material, and styrene butadiene rubber and a carboxymethyl cellulose aqueous solution were mixed as the binder in a solid content mass ratio of 96.4:1.9:1.7, and water was added as a dispersion solvent so that the solid content was 50 mass %, and further mixed to prepare a slurry solution. This slurry solution was applied to one side of a copper foil with a thickness of 10 μm so that part of the copper foil was exposed, and then the solvent was dried and removed to obtain a coating amount of 86 g / m. 2 Furthermore, the density of the negative electrode mixture was 1.45 g / cm 3 The coated area was then cut to a size of 32 mm × 52 mm and to include the exposed copper foil area, and a nickel lead piece was welded to the exposed copper foil area to obtain a negative electrode.

[0130] Preparation of non-aqueous electrolyte LiPF6 was dissolved as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio) to a concentration of 1.0 mol / L, and vinylene carbonate was further added to the solution to a concentration of 1.0 wt % to prepare a non-aqueous electrolyte solution.

[0131] <<Creating a laminated electrode body>> A 60 mm × 40 mm square was cut out from the separator to prepare sample 1. The positive electrode, sample 1, and negative electrode were stacked in this order to form a laminate. At this time, the heat-resistant B layer of sample 1 was arranged to face the positive electrode. This laminate was inserted into an aluminum laminate exterior body, and three sides, including the side where the positive and negative electrode lead pieces were exposed and the other two sides, were laminate-sealed. Next, the nonaqueous electrolyte was injected into the exterior body, and then the opening was sealed to produce a laminated electrode body.

[0132] Positive electrode unit area converted impedance (Ω cm 2 Measurement of The PTFE sheet, the laminated electrode body, and the PTFE sheet were sandwiched in a state in which they were stacked in the order of the heater block with two thermocouples embedded inside, and the heater block was further sandwiched between two metal plates, and the two metal plates were fixed with bolts and nuts so that a surface pressure of 2.0 MPa was applied to the laminated electrode body. Then, the heater block was heated, and the temperature and impedance were continuously measured using an AC electrical resistance measuring device "AG-4311" (Ando Electric Co., Ltd.) connected to the lead pieces of the positive and negative electrodes. The temperature was raised from room temperature to 280°C at a rate of 15°C / min, and the impedance was measured with an AC of 1 kHz. Then, the impedance (Ω) obtained at 40°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, and 250°C was measured using an effective positive electrode area of ​​15 cm 2 The value calculated by multiplying the impedance by the unit area of ​​the positive electrode at each temperature (Ω cm 2 ) was decided.

[0133] (8) Cycle test and nail penetration test (Preparation of batteries for use in safety tests) a. Preparation of the positive electrode LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2, carbon black as a conductive assistant, and polyvinylidene fluoride solution as a binder were mixed in a solid content mass ratio of 91:5:4, and N-methyl-2-pyrrolidone was added as a dispersion solvent so that the solid content was 68 mass%, and further mixed to prepare a slurry solution. This slurry solution was applied to both sides of an aluminum foil with a thickness of 15 μm so that part of the aluminum foil was exposed, and then the solvent was dried and removed, and the coating amount was set to 175 g / m per side. 2 Furthermore, the density of the positive electrode mixture was 2.8 g / cm 3 The coated area was then cut to a size of 30 mm×50 mm, including the exposed aluminum foil area, to obtain a positive electrode.

[0134] b. Preparation of the negative electrode Artificial graphite was mixed as the negative electrode active material, and styrene butadiene rubber and a carboxymethyl cellulose aqueous solution were mixed as the binder in a solid content mass ratio of 96.4:1.9:1.7, and water was added as a dispersion solvent so that the solid content was 50 mass %, and further mixed to prepare a slurry solution. This slurry solution was applied to both sides of a 10 μm thick copper foil so that part of the copper foil was exposed, and then the solvent was dried and removed to obtain a coating amount of 86 g / m per side. 2 Furthermore, the density of the negative electrode mixture was 1.45 g / cm 3 The coated area was then cut to a size of 32 mm × 52 mm, including the exposed copper foil area, to obtain a negative electrode.

[0135] c. Preparation of non-aqueous electrolyte LiPF6 was dissolved as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio) to a concentration of 1.0 mol / L, and vinylene carbonate was further added to the solution to a concentration of 1.0 wt % to prepare a non-aqueous electrolyte solution.

[0136] d. Battery assembly A long separator with a width of 55 mm was folded zigzag so that the active material surfaces of the positive and negative electrodes faced each other and were interposed between the positive and negative electrodes, to form a laminate consisting of 15 double-sided negative electrodes and 14 double-sided positive electrodes. At this time, the heat-resistant B layer of sample 1 was arranged to face the positive electrode. Aluminum lead pieces with sealant were welded to the exposed parts of the 14 positive aluminum foils of this laminate, and nickel lead pieces with sealant were welded to the exposed parts of the 15 negative copper foils, and then the laminate was inserted into an aluminum laminate exterior body, and the sides where the positive and negative lead pieces were exposed and the other two sides, a total of three sides, were laminated and sealed. Next, the nonaqueous electrolyte was injected into the exterior body, and then the opening was sealed to prepare a laminated type battery with 28 opposing electrodes. The resulting battery was left at room temperature for one day, and then charged at a constant current of 330 mA (0.3 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and then charged at a constant voltage to maintain 4.2 V. This method was used for the first charging after the battery was fabricated, for a total of 8 hours. The battery was then discharged at a current value of 330 mA (0.3 C) down to a battery voltage of 3.0 V.

[0137] (Cycle characteristic evaluation) The battery obtained in "d. Battery assembly" above was charged and discharged 1000 cycles in an atmosphere of 25°C. The battery was charged for a total of 3 hours by charging at a constant current of 1A (1.0C) up to a battery voltage of 4.2V, and then constant voltage charging to maintain 4.2V after reaching that voltage. The battery was discharged at a current value of 1A (1.0C) down to a battery voltage of 3.0V. The capacity retention rate was calculated from the discharge capacity at the 1000th cycle and the discharge capacity at the 1st cycle. A high capacity retention rate was evaluated as having good cycle characteristics.

[0138] (Nail penetration test) A test was conducted to cause an internal short circuit by driving a 3mm diameter iron nail into a battery charged to 4.2V at a speed of 20mm / sec, penetrating the battery. This test can clarify the phenomenon at the time of an internal short circuit by measuring the time change behavior of the voltage drop of the battery due to an internal short circuit and the behavior of the rise in the battery surface temperature due to an internal short circuit. In addition, insufficient shutdown function of the separator or rupture at low temperatures during an internal short circuit may cause the battery to suddenly heat up, which may cause the electrolyte to ignite and the battery to smoke and / or explode.

[0139] The nail penetration test was performed on 10 batteries with the same separator, and the number of batteries that did not catch fire, emit smoke, or explode, X, was calculated as the pass rate (X / 10), which is shown in Table 1.

[0140] [Method for producing silane-grafted polyolefin] The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be a propylene or butene copolymerized α-olefin. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the α-olefin polymer chain, and then trimethoxyalkoxide-substituted vinylsilane is injected to introduce alkoxysilyl groups into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate]) is added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is 3000 ppm or less.

[0141] [Production methods of modified PE and copolymers with various functional groups other than silane-modified PE] Modified PE and copolymers having various functional groups other than silane-modified PE were produced by the following methods. For each raw material, the molecular weight of the raw material used was adjusted so that the MFR was within the range of 0.5 to 10. Modified PE with hydroxyl groups was produced by saponifying and neutralizing EVA copolymer. Modified resins such as amine-modified and oxazoline-modified resins were produced by reacting the terminal vinyl groups of PE polymerized using a chromium catalyst with a tungsten-based catalyst under hydrogen peroxide conditions to convert the vinyl groups to epoxy groups. After that, the target reaction site was converted to the desired functional group using a known organic reaction for functional group conversion, and various modified PEs were obtained. After that, unreacted amines were removed through a pressure reducing valve, and the obtained amine-modified resin was extruded into strands and cut into pellets.

[0142] [Method of synthesis of resin binder] The acrylic latex used as the resin binder is produced by the following method. Into a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) were added. Next, the temperature inside the reaction vessel was raised to 80°C, and while maintaining the temperature at 80°C, 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate was added to obtain an initial mixture. Five minutes after the addition of the aqueous solution of ammonium persulfate was completed, the emulsion was dropped from the dropping tank into the reaction vessel over 150 minutes.

[0143] The above emulsion was prepared by mixing 70 parts by mass of butyl acrylate, 29 parts by mass of methyl methacrylate, 1 part by mass of methacrylic acid, 3 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) and 3 parts by mass of "Adeka Reasoap SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) as emulsifiers, 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate, and 52 parts by mass of ion-exchanged water using a homomixer for 5 minutes.

[0144] After the emulsion was added, the temperature inside the reaction vessel was kept at 80°C for 90 minutes, and then cooled to room temperature. The resulting emulsion was adjusted to pH 8.0 with 25% aqueous ammonium hydroxide solution, and a small amount of water was added to obtain an acrylic latex with a solid content of 40%. The resulting acrylic latex had a number average particle size of 145 nm and a glass transition temperature of -23°C.

[0145] [Example 1] Preparation and evaluation of separator (Preparation of polyolefin microporous membrane as substrate layer A) The resin composition of (A):(B):(C) is 30% by mass of homopolymer polyethylene (ultra-high molecular weight polyethylene (A)) with a viscosity average molecular weight of 6,300,000, 50% by mass of homopolymer polyethylene (polyethylene (B)) with a viscosity average molecular weight of 750,000, and 20% by mass of silane-grafted polyethylene (silane-modified polyethylene (C)) with an MFR of 0.4 g / min obtained by modification reaction with trimethoxyalkoxide-substituted vinylsilane. The ratio was 3:5:2. Furthermore, 1000 mass ppm of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the total, and dry blended using a tumbler blender to obtain a mixture. The obtained mixture was fed to a twin-screw extruder under a nitrogen atmosphere using a feeder. In addition, liquid paraffin (dynamic viscosity at 37.78°C: 7.59×10-5m2 / s) was injected into the extruder cylinder using a plunger pump.

[0146] The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 230°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. The melt-kneaded product was then extruded and cast onto a cooling roll whose surface temperature was controlled to 25°C through a T-die, to obtain a gel sheet (sheet-shaped molded product) with a thickness of 1350 μm.

[0147] Next, the sheet-shaped molded body was introduced into a simultaneous biaxial tenter stretching machine, and biaxial stretching was performed to obtain a stretched product. The set stretching conditions were MD magnification 7.0 times, TD magnification 6.3 times (i.e., 7 x 6.3 times), and biaxial stretching temperature 122 ° C. Next, the gel sheet after stretching was introduced into a dichloromethane tank and thoroughly immersed in dichloromethane to extract and remove liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter to perform heat setting (HS), and HS was performed at a heat setting temperature of 131 ° C. and a stretching ratio of 1.9 times, and then a relaxation operation was performed to TD 1.75 times to obtain a microporous membrane. Then, the end of the obtained microporous membrane was cut and wound up as a mother roll with a width of 1,100 mm and a length of 5,000 m.

[0148] The thickness, air permeability and porosity of the obtained polyolefin microporous membrane were measured and are shown in Table 1.

[0149] (Arrangement of heat-resistant layer B) 95 parts by mass of aluminum hydroxide oxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (solid content equivalent) of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by San Nopco, solid content concentration 40%) as an ionic dispersant were uniformly dispersed in 100 parts by mass of water to prepare a dispersion liquid. The obtained dispersion liquid was crushed with a bead mill (cell volume 200 cc, zirconia bead diameter 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, and an inorganic particle-containing slurry was prepared. 2.0 parts by mass (solid content equivalent) of the acrylic latex as the resin binder produced above was added to the dispersion liquid with the particle size distribution adjusted.

[0150] Next, the microporous membrane was continuously unwound from the microporous membrane mother roll, and one side of the microporous membrane was coated with an inorganic particle-containing slurry using a gravure reverse coater, followed by drying in a dryer at 60°C to remove water and winding up to obtain a separator mother roll.

[0151] Thereafter, the ends of the composite separator were cut off and wound up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the composite separator unwound from the mother roll was slit as necessary and used as the evaluation separator. The separator for evaluation and the battery including the same were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are shown in Table 1.

[0152] [Examples 2-8, Comparative Examples 1-3] Preparation and evaluation of separators As shown in Table 1, the molecular weight mixture composition of the polyolefin microporous film as the substrate A layer, the preparation conditions, the composite construction conditions, the thickness ratio of the substrate A layer and the heat-resistant B layer, etc. were changed, and the same operations as in Example 1 were performed to obtain the separators shown in Table 1. The obtained separators and batteries including the same were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are also shown in Table 1.

[0153] The resin composition of Comparative Example 1 was 80% by mass of a homopolymer polyethylene having a viscosity average molecular weight of 1,300,000, and 20% by mass of a silane-grafted polyethylene having an MFR of 0.4 g / min, which was obtained by modifying a polyolefin having a viscosity average molecular weight of 105,000 with a trimethoxyalkoxide-substituted vinylsilane.

[0154] The resin composition of Comparative Example 2 was 100% by mass of polyethylene homopolymer having a viscosity average molecular weight of 2,000,000.

[0155] In Example 8, a composite separator was obtained by exceptionally disposing a heat-resistant B layer having a thickness of 2.5 μm on both sides of the microporous membrane as the base material A layer. The heat-resistant B layer, which is indicated by the abbreviation in Table 1, was formed as follows.

[0156] "Ceramic composite layer" This is a heat-resistant layer B produced in the same manner as in Example 1. In Comparative Example 3, a resin binder with a glass transition point of 100° C. was used.

[0157] "PVDF-HFP / Inorganic material" Alumina (Al2O3) particles and polyvinylidene fluoride-hexafluoropropylene as a fluorine-based resin were prepared and mixed together. The mixture was then mixed with cyanoethyl polyvinyl alcohol and acetone so that the mass ratio of the mixture / cyanoethyl polyvinyl alcohol / acetone was 19.8 / 0.2 / 80. The mixture was uniformly dispersed to prepare a coating solution. This was applied to one side of a polyolefin microporous membrane using a gravure coater to form a heat-resistant B layer with the thickness shown in Table 1, and a composite separator was obtained.

[0158] "Para-aramid / inorganic material" 150 parts by mass of paraphenylenediamine was added to 5000 parts by mass of N-methyl-2-pyrrolidone (NMP) / calcium chloride solution (calcium chloride concentration = 7.1% by mass), dissolved and stirred under N2 atmosphere, then 273.94 parts by mass of terephthalic acid dichloride was added, stirred and reacted for 1 hour to obtain a polyparaphenylene terephthalamide polymerization solution. 1000 parts by mass of the polymerization solution, 3000 parts by mass of NMP, and 143.4 parts by mass of alumina (Al2O3) particles were stirred and mixed, and dispersed with a homogenizer to obtain a coating slurry. Using a drum-fixed bar coater, the coating slurry was applied to one side of a polyolefin microporous membrane under a clearance condition of 20 μm to 30 μm, and dried at a temperature of about 70 ° C. to form a heat-resistant B layer, and a composite separator was obtained.

[0159] "Meta-aramid / inorganic material" Meta-aromatic polyamide and boehmite with an average particle size of 0.6 μm were mixed at a mass ratio of 1:1, and then mixed with a mixed solvent of dimethylacetamide (DMAc) and tripropylene glycol (TPG) (mass ratio = 1:1) so that the meta-aromatic polyamide concentration was 3 mass% to obtain a coating slurry. The coating slurry was applied to one side of a polyolefin microporous membrane using a Mayer bar coater under a clearance condition of 20 μm to 30 μm to obtain a coated separator. The coated separator was immersed in a coagulation liquid with a mass ratio of water:DMAc:TPG = 2:1:1 and a temperature of 35°C, followed by water washing and drying to form a heat-resistant B layer, and a composite separator was obtained.

[0160]

Table 1-1

[0161]

Table 1-2

Claims

1. A battery separator including a polyolefin microporous membrane for use in a nonaqueous electrolyte secondary battery having a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a nonaqueous electrolyte solution obtained by dissolving an electrolyte in a nonaqueous solvent, The polyolefin microporous membrane includes a base material A layer, and a heat-resistant B layer is laminated on at least one surface of the base material A layer, The heat-resistant B layer includes at least one selected from the group consisting of ceramic, aramid resin, and polyvinylidene fluoride (PVDF); the battery separator includes a silane-modified polyolefin, and when the battery separator comes into contact with an electrolyte solution, a silane crosslinking reaction of the silane-modified polyolefin is initiated; The impedance measured at any of the temperatures of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C was 5,000 to 350,000 Ω cm 2 That is, a battery separator.

2. A battery comprising an electrode, the battery separator according to claim 1, and a non-aqueous electrolyte.

3. The battery according to claim 2 , wherein the non-aqueous electrolyte solution contains a non-aqueous solvent and a lithium salt.

4. The following two elements: (1) an exterior housing housing a positive electrode, a negative electrode, and a laminate or wound body of the battery separator according to claim 1; and (2) a container containing a non-aqueous electrolyte; A battery assembly kit comprising:

5. The battery assembly kit according to claim 4 , wherein the non-aqueous electrolyte solution contains a fluorine (F)-containing lithium salt.

6. The non-aqueous electrolyte solution is lithium hexafluorophosphate (LiPF 6 6. The battery assembly kit according to claim 4 or 5, comprising:

7. 7. The battery assembly kit according to claim 4, wherein the non-aqueous electrolyte solution is an acid solution and / or a base solution.

8. The following steps: A step of preparing a battery assembly kit according to any one of claims 4 to 7; a step of initiating a silane crosslinking reaction of the silane-modified polyolefin by contacting the battery separator in element (1) of the battery assembly kit with the non-aqueous electrolyte in element (2); A method for manufacturing a battery comprising the steps of:

9. moreover, Performing at least one charge / discharge cycle A method for producing the battery of claim 8, comprising:

Citation Information

Patent Citations

  • Porous film, and separator for cell and cell using the same

    JP1997216964A

  • Porous membrane, battery separator comprising porous membrane, and manufacture thereof

    JP1999144700A

  • Porous film, battery separator comprising porous film, and its production

    JP1999172036A

  • Self-supporting, heat-resistant microporous film for use in energy storage devices.

    JP2012521615A

  • Porous film and separator for batteries comprising porous film

    WO1997044839A1